2016
DOI: 10.1007/s11427-016-0051-8
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of stature by using the dimensions of the right hand and right foot in Han Chinese adults

Abstract: The Han Chinese people are the main ethnic group in China and the largest ethnic group in the world. The dimensions of the hands and feet have been successfully used for the estimation of stature. A total of 26,927 healthy adult subjects, comprising 13,221 men and 13,706 women, were recruited. The survey samples were chosen through random cluster sampling. The mean values were significantly higher in men than those in women for all measurements (P<0.001). All the measurements showed a statistically significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 55 publications
(58 reference statements)
3
9
0
Order By: Relevance
“…Krishan and Sharma, in a study in India, also reported a significant correlation between foot length and stature in Indian adolescents (r=0.741 for boys) (r=0.734 for girls), which were similar to the findings of the current study [21]. However, the correlation scores between foot length and stature among Chinese adolescents in this study were lower than those previously reported in our previous study of Chinese children’s foot shape [22], and higher than those previously reported in a study of Chinese adult foot shape (Figure 7) [23]. Xu et al found a significant correlation between foot length and stature among Chinese children aged 7–12 years of age (r=0.792 for boys) and (r=0.747 for girls) [22].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Krishan and Sharma, in a study in India, also reported a significant correlation between foot length and stature in Indian adolescents (r=0.741 for boys) (r=0.734 for girls), which were similar to the findings of the current study [21]. However, the correlation scores between foot length and stature among Chinese adolescents in this study were lower than those previously reported in our previous study of Chinese children’s foot shape [22], and higher than those previously reported in a study of Chinese adult foot shape (Figure 7) [23]. Xu et al found a significant correlation between foot length and stature among Chinese children aged 7–12 years of age (r=0.792 for boys) and (r=0.747 for girls) [22].…”
Section: Discussionsupporting
confidence: 89%
“…Xu et al found a significant correlation between foot length and stature among Chinese children aged 7–12 years of age (r=0.792 for boys) and (r=0.747 for girls) [22]. Zhang et al found a significant correlation between foot length and height in Chinese adults (r=0.602 in men) and (r=0.565 in women) [23]. The process of maximal growth in height, limb length, and foot length vary in time in childhood and adolescence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 43 ] The largest difference in hand breadth was observed between Saudi men and Australians (right side: 1.90, left side: 1.87), [ 48 ] and the smallest difference was observed for the left side between Saudi men and Egyptians (0.02), [ 43 ] and for the right side between Saudi men and Chinese Han individuals (0.02). [ 49 ] Large differences in palm length were observed between Saudi men and Australians [ 21 , 48 ] or Koreans. [ 50 ] Most of the finger measurements exhibited medium to very large differences between Saudi men and the other populations.…”
Section: Discussionmentioning
confidence: 99%
“…[ 55 ] My findings regarding bilateral hand breadth differences agree with other findings among Australians, [ 48 ] northern and southern Indians, [ 31 ] and Rajput Indians, who had significantly broader right hands. [ 55 ] Nevertheless, no significant differences in hand length and breadth were observed in studies of Iban Malaysians, [ 47 ] Chinese individuals, [ 49 ] and Slovaks. [ 46 ] Saudi men had generally symmetrical finger lengths, with the exception of the little finger, which conflicts with reported asymmetry in the thumb and ring fingers of Iban Malaysians and in the ring fingers of northeastern Indians.…”
Section: Discussionmentioning
confidence: 99%